Juveniles sentenced to life in Australia - empirical findings - Deegan, Simone (The Routledge international handbook of juvenile homicide, 2024)
In Chapter 12 of this handbook, I argued that homicides committed by young people are rare, with the bulk of killings the result of spontaneous male-on-male attacks or fights that went well beyond their projected outcomes. Accordingly, many young “killers” come before the courts as first-time offenders, despite, in most cases, a long history of behavioral problems and deeply unsettled lives. This chapter outlines how avenues to a murder conviction ultimately converge and result in the kind of pain for juvenile homicide offenders that only a sentence of life imprisonment can levy. Essentially, this chapter is about 19 young people and their struggles within custodial facilities – where they have spent 100% of their days from middle adolescence – to build and claim a master status that breaks free of the murderer/lifer dyad. Building on Chapter 12, this chapter relays the way that “life” curtails their futures, hurts their families, and frequently undermines their attempts to walk different paths.